Dampak Perundungan Lisan terhadap Kecerdasan Interpersonal Peserta Didik Sekolah Dasar - Muyasari, Nila; Sunarso, Ali (Kuras Institute, 2025)
Interpersonal intelligence is a crucial aspect of student development, particularly in fostering healthy social relationships. However, verbal bullying in the school environment can negatively impact interpersonal intelligence. This study aims to analyze the effects of verbal bullying on the interpersonal intelligence of sixth-grade students at State Elementary School (SDN) Pesurungan Kidul 2 Tegal. This research employed a mixed-method approach, incorporating both qualitative and quantitative data collection techniques. A total of 35 respondents—including teachers, students, and parents—participated in this study. Qualitative data were gathered through observations and in-depth interviews, while quantitative data were collected using a structured questionnaire. The data were analyzed through data reduction, data presentation, conclusion drawing, and thematic analysis. The findings reveal that verbal bullying contributes to a decline in students’ interpersonal intelligence, characterized by reduced empathy, low self-confidence, and difficulties in collaboration. The quantitative results indicate that 77% of students experience negative impacts such as anxiety, insecurity, sadness, and difficulties in social interaction and teamwork. This study underscores the need for school intervention policies, including anti-bullying education programs and increased teacher involvement in monitoring students' social interactions.